The effect of continuous confined strip shearing deformation on the mechanical properties of AZ31 magnesium alloys - Peng, Jinhua (2020)
Continuous confined strip shearing deformation (CCSS) was conducted on AZ31 magnesium alloys. The microstructure and texture were modified and special inclined basal texture was obtained through different routes. The newly formed basal texture was favor for the basal slip which brought about lower micro-hardness and yield strength but higher elongation. The strong tensile-compression asymmetry in the base material was weakened because basal slip was the dominating deformation mechanism both in tensile and compression tests. Meanwhile, {10-12} twinning was suppressed because of easier activation of basal slip. The strain hardening behavior was also changed and the strain hardening rate almost decreased along the whole deformation process; and only a slight increase was found at the stage2 of route A in tensile test. The strain hardening exponents were scattered from different stages due to the specific deformation mechanism at each stage.